L’article 7 de la Charte canadienne et la discipline carcérale - Garant, Patrice; Halley, Paule (Revue générale de droit, 1989)
Disciplinary sanctions against prisoners like any other decision taken by prison authorities are administrative decisions. That qualification had up to recently the effect of withdrawing those decisions from the supervisory jurisdiction of superior courts. Under such circumstances, the prisoner was the subject of an in-house justice guided by reasons of administrative commodity rather than by the respect of his rights, because he had indeed no right.